Analisa Pengaruh Variasi Media Pendingin Pada Proses HeatTreatment Metode Hardening-Tempering Material Baja S45C Terhadap Sifat Mekanik dan Struktur Mikro - Aldi Wahyu Permana; Ratna Dewi Anjani; Iwan Nugraha Gusniar (Jurnal Rekayasa Mesin, 2020)
In Our life, we always life with any tools and technology for improve our life. We can find many tools and other technolgy are made from metal. Of course, we need metals which have a characteristic for improve that inquiry, for example in terms of hardness in metal. Metal hardness can be increased in several ways. One of them is the hardening process. This process is a process of heat treatment of metal by heating and then cooling it to a certain temperature. In the traditional market, a lot of shredded coconut water is not used and can be used as a cooling medium in the hardening process. Therefore, the author will use the results of this wate shredded coconut water as a cooling medium for the hardening process.  Researchers  examined  the  effect  of  variations in heat  treatment  process  cooling media  on mechanical properties and microstructure with three variations of coolant. temperature 865 ⁰C for hardening process and 465 C for tempering process. research activities include hardness and micro structure testing. The results showed that the hardening process salt water cooling medium had the highest hardness value of 275.6Hv while the lowest hardness was  obtained in the coconut water cooling medium  which had carried out the tempering process with a hardness of 219.3Hv. This is influenced by SOQ (Severity Of Quenching) or what is called the ability of the cooling media, for salt water the value is 5.0 for SOQ and for coconut water below 2.055. Meanwhile, for the microstructure, it can be seen that the hardening process brine cooling medium has a finer structure than the other cooling specimens. Meanwhile, in the tempering process, martensite turned into finer ferrite cementite with a hardness of 269.3Hv